Complete chloroplast genomes of two Ainsliaea species and the phylogenetic analysis in the tribe Pertyeae - Chen, Xinyu; Feng, Yifan; Qu, Tianmeng; Chen, Hui; Liu, Xiaofeng; Pang, Liang; Chen, Ming; Fu, Zhixi (Frontiers in Genetics, 2024)
The genus Ainsliaea DC. is one of the major groups within the tribe Pertyeae (Asteraceae). It comprises several important Chinese medicinal species. However, the phylogenetic position has undergone a long process of exploration. The complete chloroplast (cp) genome sequences data has not been employed in species identification and phylogeny of Ainsliaea. In this study, the complete cp genomes of two Ainsliaea species (A. gracilis and A. henryi) were reported, followed by structural, comparative, and phylogenetic analyses within the tribe Peryteae. Both cp genomes displayed a typical quadripartite circular structure, with the LSC and SSC regions separated by the IR regions. The genomes were 152,959 (A. gracilis) and 152,805 (A. henryi) base pairs (bp) long, with a GC content of 37.6%. They were highly conserved, containing 134 genes, including 87 protein-coding genes, 37 tRNA genes, 8 rRNA genes, and 2 pseudogenes (rps19 and ycf1). Moreover, thirteen highly polymorphic regions (e.g. trnK-UUU, trnG-UCC, trnT-GGU, accD-psaI, and rpl22-rps19) were identified, indicating their potential as DNA barcodes. The phylogenetic analysis confirmed the placement of Ainsliaea in the tribe Pertyeae, revealing close relationships with the genera Myripnois and Pertya. In comparison with Ainsliaea, Myripnois was more closely related to Pertya. This study lays a theoretical foundation for future research on species identification, population genetics, resource conservation, and sustainable utilization within Ainsliaea and Pertyeae.